New perspectives on health, disability, welfare and the labour market - Lindsay, Colin (Researcher); Greve, Bent; Cabras, Ignazio; Ellison, Nicholas, 1952-; Kellett, Steve (Psychologist) (Broadening perspectives on social policy, 2015)
Bringing together researchers from the fields of social policy, economics, sociology and clinical psychology, this book offers new evidence on the inter-related problems faced by disability claimants, and identifies important lessons for policy. Explores how reducing the level of UK benefit claiming among those with health limitations has been a priority for successive governments Argues that current policy fails to reflect the evidence that people on long-term disability benefits face a complex combination of barriers to work and social inclusion Demonstrates that there is a need for conti.